2011
DOI: 10.1158/1078-0432.ccr-11-0072
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 Inhibition Is Effective in Breast Cancer: A Phase II Trial of Tanespimycin (17-AAG) Plus Trastuzumab in Patients with HER2-Positive Metastatic Breast Cancer Progressing on Trastuzumab

Abstract: Purpose: HSP90 is a chaperone protein required for the stability of a variety of client proteins. 17-Demethoxygeldanamycin (17-AAG) is a natural product that binds to HSP90 and inhibits its activity, thereby inducing the degradation of these clients. In preclinical studies, HER2 is one of the most sensitive known client proteins of 17-AAG. On the basis of these data and activity in a phase I study, we conducted a phase II study of 17-AAG (tanespimycin) with trastuzumab in advanced trastuzumab-refractory HER2-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
280
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(291 citation statements)
references
References 41 publications
9
280
0
2
Order By: Relevance
“…For example, several potent, structurally diverse HSP90 inhibitors are currently in clinical trials. In breast cancer, the focus to date has been on HER2-positive disease, where addition of the firstgeneration HSP90 inhibitor tanespimycin (17-AAG) to trastuzumab therapy has demonstrated efficacy in patients who had previously progressed on trastuzumab alone (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several potent, structurally diverse HSP90 inhibitors are currently in clinical trials. In breast cancer, the focus to date has been on HER2-positive disease, where addition of the firstgeneration HSP90 inhibitor tanespimycin (17-AAG) to trastuzumab therapy has demonstrated efficacy in patients who had previously progressed on trastuzumab alone (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…A phase 2 clinical trial showed efficacy of an HSP90 inhibitor when combined with trastuzumab in the treatment of HER2-overexpressing metastatic breast cancer. 97 Nevertheless, the HSP90 approach has been in development for over a decade in patients with advanced breast cancer without clear evidence of clinical efficacy. A30, an RNA aptamer specific to the extracellular domain of HER3, is able to inhibit NRG-induced signaling.…”
Section: Others Indirect Strategiesmentioning
confidence: 99%
“…(7) Inhibiting the heat shock protein 90 (HSP90), and consequently HER3 maturation and refolding, is another way to reduce HER3 stabilization. 97 (8) HER3 can be targeted by small RNA aptamer molecules, which bind with the extracellular domain of HER3 and inhibit downstream signaling. 98 (9) Using a peptidomimetic molecule binding HER2 and mimicking HER2-HER3s dimerization site is another way to prevent HER3 activation.…”
Section: Others Indirect Strategiesmentioning
confidence: 99%
“…Her team is evaluating one such drug, BYL719, and has also seen promising results from another approach to bolstering HER2-targeted treatment. Tumour cells rely on a molecule called heat-shock protein 90 (HSP90) to manage the production of HER2, and Modi and colleagues have found that chemical inhibition of HSP90 can stall HER2-dependent tumour growth 7 . "In our first phase 2 trial, we combined an HSP90 inhibitor with Herceptin and saw a nearly 25% response rate from just these two agents, without any chemo," she says.…”
Section: Targeted Therapymentioning
confidence: 99%